German Industrial Organization since the World War - Liefmann, Robert (Quarterly Journal of Economics, 1925)
Industrial combinations before the war, 82. — State regulation of cartels during the war, 87. — Effects of the socialization movement, 90. — Reorganizations in the potash, coal, iron, and electrical industries, 90. — Formation of "concerns" after the war, 93. — Comparative advantages of different types of combination, 96. — Decline of the cartel movement after the war only temporary, 99. — The coal and iron syndicates, 101. — Regulatory legislation of November, 1923, and its results, 106. — Further problems, 109.